1991
DOI: 10.1161/01.hyp.18.5.622
|View full text |Cite
|
Sign up to set email alerts
|

Role of chloride in angiotensin II-induced salt-sensitive hypertension.

Abstract: The present study investigated the effect of the anion accompanying sodium on the development of angiotensin II-induced hypertension in rats and the role of the sympathetic nervous system and extracellular fluid volume in its mechanism. Hypertension was induced by intraperitoneal infusion of angiotensin II (125 ng/min) for 12 days via miniosmotic pump. High dietary intake of sodium chloride significantly augmented the angiotensin II-induced hypertension (mean blood pressure on day 13,165±6 versus 142±6 mm Hg,/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…In addition, these findings may provide a link between increased chloride reabsorption in the early distal tubule in salt-sensitive hypertension and blood pressure elevation (Kirchner, 1990;Roman & Kaldunski, 1991) and, conversely, between the defect in chloride reabsorption in the loop of Henle and the hypotension in Bartter's syndrome (Gill & Bartter, 1978). This effect of chloride on vasoactivity may explain the requirement for chloride as the anion accompanying sodium in salt-sensitive (Boegehold & Kotchen, 1989) and AII-dependent (Passmore & Jimenez, 1991;Sato et al, 1991) models of hypertension. Finally, the results of the present study support the hypothesis that the ability of high chloride to increase RVR and lower GFR is due, at least in part, to the ability of chloride to modify responsiveness of the kidney to pressor agents.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, these findings may provide a link between increased chloride reabsorption in the early distal tubule in salt-sensitive hypertension and blood pressure elevation (Kirchner, 1990;Roman & Kaldunski, 1991) and, conversely, between the defect in chloride reabsorption in the loop of Henle and the hypotension in Bartter's syndrome (Gill & Bartter, 1978). This effect of chloride on vasoactivity may explain the requirement for chloride as the anion accompanying sodium in salt-sensitive (Boegehold & Kotchen, 1989) and AII-dependent (Passmore & Jimenez, 1991;Sato et al, 1991) models of hypertension. Finally, the results of the present study support the hypothesis that the ability of high chloride to increase RVR and lower GFR is due, at least in part, to the ability of chloride to modify responsiveness of the kidney to pressor agents.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, when ANG II was clamped, the progressive increase in body fluid volume and renal interstitial pressure became excessive (or inappropriate) to the existing plasma or renal levels of ANG II. The word inappropriate may be more pertinent because the hypertensinogenic effect of ANG II was produced in the presence of volume expansion that was not different from animals that did not receive ANG II and remained normotensive, although many other investigators have shown that increased sodium intake causes a marked potentiation of ANG II pressor effect (6,35,74,108,142,154). DeClue et al (36) was the first to demonstrate that a dissociation between extracellular fluid volume and the plasma or perhaps tissue levels of ANG II may be an important alteration underlying the development of high blood pressure.…”
Section: The Effects Of Sodium Intake On the Pressor Response To Ang IImentioning
confidence: 99%
“…24,26 It is well established that chronic low-dose Ang II infusion is a salt-sensitive model of hypertension, and there is evidence to suggest that the additional hypertensive effect of salt is mediated by sympathetic nervous system activation. 13,[27][28][29][30] Although the most compelling evidence for sympathetic nervous system activation in response to salt is described in rats, 13,[27][28][29][30] it has also been demonstrated recently in rabbits 31 using repeated assessment of response to ganglionic blockade. More importantly, there is considerable evidence that neurogenic mechanisms may play a role in the pathophysiology of salt sensitivity in human essential hypertension.…”
mentioning
confidence: 99%